Effects of postbiotics and paraprobiotics as replacements for antibiotics on growth performance, carcass characteristics, small intestine histomorphology, immune status and hepatic growth gene expression in broiler chickens - Danladi, Yohanna; Loh, Teck Chwen; Foo, Hooi Ling; Akit, Henny; Md Tamrin, Nur Aida; Azizi, Mohammad Naeem (Multidisciplinary Digital Publishing Institute, 2022)
Background: This experiment was designed to investigate how replacing antibiotics with postbiotics and paraprobiotics could affect growth performance, small intestine morphology, immune status, and hepatic growth gene expression in broiler chickens. Methods: The experiment followed a completely randomized design (CRD) in which eight treatments were replicated six times with seven birds per replicate. A total of 336, one-day-old (COBB 500) chicks were fed with the eight treatment diets, which include T1 = negative control (Basal diet), T2 = positive control (Basal diet + 0.01% (w/w) Oxytetracycline), T3 = Basal diet + 0.2% (v/w) postbiotic TL1, T4 = Basal diet + 0.2% (v/w) postbiotic RS5, T5 = Basal diet + 0.2% (v/w) paraprobiotic RG11, T6 = Basal diet + 0.2% (v/w) postbiotic RI11, T7 = Basal diet + 0.2% (v/w) paraprobiotic RG14, T8 = Basal diet + 0.2% (v/w) paraprobiotic RI11, for 35 days in a closed house system. Results: The growth performance indicators (final body weight, cumulative weight gain, and feed conversion ratio) were not significantly (p > 0.05) affected by the dietary treatments. However, feed intake recorded a significant (p < 0.05) change in the starter and finisher phases across the dietary treatments. Paraprobiotic RG14 had significantly (p < 0.05) lower abdominal fat and intestines. Villi heights were significantly (p < 0.05) increased, while the crypt depth decreased significantly due to dietary treatments. The dietary treatments significantly influenced colon mucosa sIgA (p < 0.05). Similarly, plasma immunoglobulin IgM level recorded significant (p < 0.05) changes at the finisher phase. In this current study, the hepatic GHR and IGF-1 expressions were significantly (p < 0.05) increased by postbiotics and paraprobiotics supplementation. Conclusions: Therefore, it was concluded that postbiotics and paraprobiotics differ in their effect on broiler chickens. However, they can replace antibiotics without compromising the growth performance, carcass yield, and immune status of broiler chickens.